1995
DOI: 10.1159/000236997
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Functions of a Pool of Arachidonic Acid Associated with Triglycerides in Human Inflammatory Cells

Abstract: The distribution of arachidonic acid (AA) within intracellular lipid pools of inflammatory cells is thought to be an important factor regulating the production of eicosanoids. We have recently identified a pool of AA associated with triglycerides (TGs) in human lung macrophages. This pool is also present in other human inflammatory cells (mast cells, eosinophils, monocytes and platelets) and it contains a percentage of total cellular AA ranging from 10 to 45%. Kinetic studies of AA incorporation have shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 9 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…Those morphological differences may reflect differences in lipid composition and/or ratio neutral lipids/ phospholipids within lipid bodies. Typically, increases in lipid body size and numbers are accompanied by accumulation of neutral lipids in their hydrophobic core (10,45). Indeed, lipid analysis from BCGinfected macrophages demonstrated significant and time-dependent increases in the cellular pool of triglycerides and cholesterol esther (C. Maya-Monteiro, H. D'Avila, and P. Bozza, unpublished observations).…”
Section: Discussionmentioning
confidence: 96%
“…Those morphological differences may reflect differences in lipid composition and/or ratio neutral lipids/ phospholipids within lipid bodies. Typically, increases in lipid body size and numbers are accompanied by accumulation of neutral lipids in their hydrophobic core (10,45). Indeed, lipid analysis from BCGinfected macrophages demonstrated significant and time-dependent increases in the cellular pool of triglycerides and cholesterol esther (C. Maya-Monteiro, H. D'Avila, and P. Bozza, unpublished observations).…”
Section: Discussionmentioning
confidence: 96%
“…AA is thought to be released from cellular glycerolipids for the regulation of eicosanoid biosynthesis in inflammatory cells. However, it has been reported that TGs may act as a rapid reacylation pool for AA released during human lung macrophage activation (Triggiani et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, increases in the size and numbers of lipid bodies are accompanied by accumulation of triacylglycerides and cholesterol esters in their hydrophobic core. 56,57 In different cell systems, including adipocytes and macrophages, intracellular lipids are stored and metabolized in hydrophobic organelles called lipid bodies or lipid droplets. Although lipid bodies were long considered inert fat depots, lipid bodies are now viewed as dynamic organelles with roles in integrating lipid metabolism, inflammatory mediator production, membrane trafficking and intracellular signaling.…”
Section: Leptin and Mtor: Partners In Macrophage Metabolism And Activmentioning
confidence: 99%